ANALYSIS OF TEACHERS' USE OF ENGLISH INSTRUCTIONAL MATERIALS: FROM PREPARATION TO IMPLEMENTATION :A Case Study of English Instructional Material Use by English Teachers at STIA LAN Bandung - Aminuddin, Muhammad (2009)
The English instructional materials have played important role in English Language Teaching. However, this important role is not followed by the teachers' use of materials and students' responses toward the material use which are believed to contribute to the improvement of the quality of teaching. Therefore, this study attempts to analyze how the teachers use the materials and how the students respond to their teachers' material use. The study employed a qualitative research design with a case study. The data were taken from several sources including document analysis (i.e. lesson plans and textbook units), classroom observation (to record implemented classroom activities), teachers' semi-structured interviews, and students' questionnaires (students' responses to seven multi-choice questions provided). There were eight teachers at STIA LAN Bandung participated in this study. The study revealed that the teachers used the materials differently, and they were found out to use other material sources outside the coursebook. The data showed that the teachers modified the materials during the preparation and implementation processes, and in using the materials, the study found that they experienced difficulties due to unfamiliar and irrelevant contents of the materials, how to organize activities, unclear instruction, students' enthusiasm, and time constraints. In relation to the students' responses to their teachers' material use, the study found that the students acknowledged their teachers' competency in using the materials which they considered that the learning materials have met students' needs. With these findings, it can be concluded that the use of materials vary and the modification to the materials is inevitable. Therefore, the study recommends that in order to improve teachers' use of materials, teachers should be given a teacher training where they are trained on how to modify the materials as to provide more relevant and familiar materials to the students and how to implement the materials as to improve teachers' use of materials in the classroom.